Erased : what American patriarchy has hidden from us - Tubbs, Anna Malaika (Flatiron Books, 2025)
"The new book from the New York Times bestselling author of The Three Mothers. In Erased, Anna Malaika Tubbs recovers all that American patriarchy has tried to destroy. Across the world, patriarchy has oppressed women and denied their contributions, but every nation has its own unique gendered hierarchy. Dr. Anna Malaika Tubbs applies her signature approachable yet rigorous analysis to define American patriarchy in this definitive and groundbreaking history. Humanity in the United States is determined by gender in a limited and flawed binary logic that is also always tied to whiteness. Tubbs shows how a fabricated hierarchy became so deeply ingrained in the country over time that it now goes unnoticed, along with everything it intentionally conceals. From the founding fathers to the current Supreme Court justices, from the treatment of enslaved women to the American maternal health crisis, from the exclusion of women in the Constitution to the continued lack of an Equal Rights Amendment, Tubbs brings together academic research, the stories of freedom fighters both past and present, and her own experiences to reveal what is erased in the wake of American patriarchy. The system has survived by hiding the tools that are necessary to dismantle it. But Tubbs beautifully reminds us that those tools, including our intuition, courage, ancient wisdom, and power, are still well within our reach. Erased is the story of the United States from a new perspective: one where the people who shaped this country--who have been oppressed and whose contributions have been denied--are at the center, reminding us that we can restore what has been strategically kept from us. Once again, Dr. Anna Malaika Tubbs has written a book that will be a touchstone for conversations on gender, race, and equity for years to come"--